Probing valley population imbalance in transition metal dichalcogenides via temperature-dependent second harmonic generation imaging - Leonidas Mouchliadis (Nature Portfolio, 2021)
Abstract Degenerate minima in momentum space—valleys—provide an additional degree of freedom that can be used for information transport and storage. Notably, such minima naturally exist in the band structure of transition metal dichalcogenides (TMDs). When these atomically thin crystals interact with intense laser light, the second harmonic generated (SHG) field inherits special characteristics that reflect not only the broken inversion symmetry in real space but also the valley anisotropy in reciprocal space. The latter is present whenever there exists a valley population imbalance (VPI) between the two valleys and affects the polarization state of the detected SHG. In this work, it is shown that the temperature-induced change of the SHG intensity dependence on the excitation field polarization is a fingerprint of VPI in TMDs. In particular, pixel-by-pixel VPI mapping based on polarization-resolved raster-scanning imaging microscopy was performed inside a cryostat to generate the SHG contrast in the presence of VPI from every point of a TMD flake. The generated contrast is marked by rotation of the SHG intensity polar diagrams at low temperatures and is attributed to the VPI-induced SHG.